Diversifying Soybean Production Risk Using Maturity Group and Planting Date Choices. (1st September 2016) - Weeks, Wes; Popp, Michael P.; Salmeron, Montserrat; Purcell, Larry C.; Gbur, Edward E.; Bourland, Fred M.; Buehring, Normie W.; Earnest, Larry; Fritschi, Felix B.; Golden, Bobby R.; Hathcoat, Daniel; Lofton, Josh; et al.
Abstract : While soybean [ Glycine max (L.) Merr.] production risk is typically managed by planting a range of maturity groups (MGs) across a few different planting dates (PDs), there have been no reports that have quantified changes in risk and profitability using this diversification strategy. Three years of field‐trial data from eight locations in six states were analyzed to determine risk–return tradeoffs across MG and PD. Producer revenue expectations were adjusted by soybean harvest date, assessing oil and meal premiums or discounts, and differential irrigation requirements by MG and PD, whereas costs for seed, fuel, fertilizer, equipment, and chemicals were held constant. Using portfolio theory, an efficient frontier—maximizing net returns for a given level of risk or minimizing risk for a given level of net return—was estimated by location. Cultivars from MG III and MG IV had higher expected net returns than MG V and VI at all locations. Early‐season planting combinations were found to be riskier than the three successive planting dates but led to oil, protein, and seasonal sale price premiums. Across different environments, selecting two to six MG×PD combinations was sufficient to lower risk by 29 to 40% when compared to the single, profit‐maximizing MG×PD choice. Depending on location, this risk reduction decreased net returns between 2 and 22% when compared to the profit‐maximizing MG×PD choice. Core Ideas Producers often like to diversify by planting across a range of dates and maturity groups. Diversification is common but risk–return tradeoffs have not been meaningfully quantified. Early‐season planting combinations were riskier but led to sale price premiums. Using two to six combinations lowered risk by 29–40% but decreased returns by 2–22%.